Analysis of Special Library National Standards in Indonesia: Integrative Literature Review - Anita Tri Widiyawati; Kanyarat Kwiecien (AL Maktabah, 2023)
Special libraries have a crucial role in maintaining government and non-government organizations. Based on this, the Head of the National Library of the Republic of Indonesia issued National Standards for Special Libraries, which serve as guidelines for the organization and management of all types of special libraries in Indonesia, namely Regulation of the Head of the National Library of the Republic of Indonesia Number 7 of 2022 concerning National Standards for Special Libraries. This research aims to theoretically analyze the standard indicators in the Regulation of the Head of the National Library of the Republic of Indonesia Number 7 of 2022 concerning National Special Library Standards. The method used in this research is a literature review study using an integrative literature review. The findings from this research are that seven indicators need to be included in the standards, namely: (1) Disaster mitigation standards for library collections and buildings; (2) Fulfillment of library collection types for disabled users, especially people who are blind; (3) Forming a committee to formulate library collection development policies; (4) Collections acquisition is carried out through purchases, grants, resource sharing, own production, and deposits or loans; (5) Adding bibliotherapy services to the types of library services and developing mental health literacy; (6) The minimum educational qualification of a librarian is Diploma 3 (D-III) in the field of Library, Documentation and Information Science; and (7) The requirements for members and/or administrators of professional organizations in the field of librarianship need to be revised, namely the existence of limitations on the educational qualifications of librarians.